Impact of glycemic treatment and blood glucose monitoring on outcomes in patients with acute ischemic stroke without prior diabetes: a longitudinal cohort study - Hsi-Hsing Yang; Wu-Chien Chien; Jen-Jiuan Liaw; Chia-Chen Yang; Chi-Hsiang Chung; Shi-Hao Huang; Yao-Ching Huang; Bing‑Long Wang; Ren-Jei Chung; Peng-Ciao Chen; Ting-Ti Lin; Pi-Ching Yu; et al. (Diabetology & Metabolic Syndrome)
Abstract Objectives To explore the short- and long-term effects of glycemic management—through glycemic treatment and blood glucose monitoring (BGM)—on stroke recurrence and mortality specifically in patients experiencing a first-ever ischemic stroke (FIS) with hyperglycemia (FISHG) who have not previously been diagnosed with diabetes mellitus (DM). Methods We gathered data on patients who were registered on Taiwan’s National Health Insurance Research Database from 2000 to 2015. We one-fold propensity-score-matched (by sex, age, and index date) 207,054 patients into 3 cohorts: those with FIS (1) without hyperglycemia, (2) hyperglycemia without glycemic treatment, and (3) hyperglycemia with glycemic treatment. We used Cox proportional hazard regression to evaluate the short- (within 1 year after FIS) and long-term (9.3 ± 8.6 years after FIS) prognostic effects of glycemic management on stroke recurrence and mortality of FISHG. Results Stroke recurrence and mortality were significantly more likely in the patients with FISHG than their counterparts without hyperglycemia (p < 0.05). Under glycemic treatment, patients with FISHG demonstrated lower risk of mortality at every follow-up than those without (p < 0.001) but were not less likely to have stroke recurrence (p > 0.05). Integrating BGM with glycemic treatment in the FISHG cohort significantly reduced the risk of stroke recurrence compared to patients receiving only glycemic treatment at 1-month, 3-month, 6-month, and 1-year post-stroke follow-ups (adjusted hazard ratios = 0.84, 0.90, 0.88, and 0.92, respectively); additionally, this approach significantly decreased mortality risk at each post-stroke follow-up period (p < 0.05). Conclusions BGM combined with glycemic treatment significantly improves prognosis in patients with FISHG who have not been previously diagnosed with DM, reducing the risks of stroke recurrence and mortality.